The correlation between denture usage satisfactions on quality life of the elderly - Fuad H. Akbar; Ayub I. Anwar (DiscoverSys Inc., 2017)
Objective: To analyze correlation between the denture use satisfactions and quality life of elderly and the relationship between gender and denture use satisfactionMaterial and Methods: This study is an observational analytical study. The sample of study is elderly population aged â‰¥50 years who live in Luwu Timur, South Sulawesi, the sample was to fill the questioner form based on OHIP-EDENT from WHO. The Chi-square test was used to analyze the relationship between gender and denture use satisfactions.Results: Spearmanâ€™s correlation test results for each domain OHIP-EDENT and OHIP-EDENT total showed a significant correlation of (p < 0.05) between denture use satisfaction and functional limitations, physical pain, psychological discomfort, and physical disability domain showed significant. Meanwhile, chi-squared test for denture use satisfactions to gender does not have a significant relationship.Conclusion: The denture use satisfactions has no correlation to quality of life of older adults. The gender dose not influence the satisfactions in denture use.